Pathological features of the structure of the female genital organs from fetuses of mothers with complicated pregnancies - L. S. Kupriyanova (Zaporožskij Medicinskij Žurnal)
Aim. In the course of the study the structural features of fetal ovarian of mothers with severe preeclampsia in comparison with fetuses from healthy mothers were revealed.